Professional Baseball Pitchers Use of Weighted Ball Training, Injury Incidence, and Time Loss: A Preliminary Study - Ellen Shanley; Thomas J. Noonan; Michael J. Kissenberth; Daniel Kline; Charles A. Thigpen; Garrett S. Bullock (International Journal of Sports Physical Therapy)
# Background Little is known about the injury risk associated with weighted ball use by professional baseball pitchers. The purpose of this study was to describe weighted ball training and injuries and compare injury rates between those professional pitchers using weighted ball training and those that did not use weighted ball training during the 2023 pre- and regular season.